Gauging acceptance: a multifaceted examination of physical ability and its role for peer networks in adolescent physical education - Holler, Cornelius; Schüßler, Annabell (Journal of early adolescence, 2025)
This study examines the role of perceptions of physical ability on collaboration networks in physical education through three distinct lenses: self-concept, peer assessments, and teacher ratings. The interplay of these perspectives on team partner nominations is analyzed using exponential random graph models, while taking into account variables such as liking networks and gender associations. Drawing upon a sample of 302 adolescents across 14 high-school classes, the results reveal that physical ability is significantly linked with choices for team partners, indicating that high and similar performing peers are more likely to be chosen as team partners. Furthermore, only peer perceived ability was found to be predictive of social relationships in physical education, while the self and teacher perspectives show no significant effects on collaboration choices in sports games. These findings highlight the important role of academic norms, such as physical ability, for peer relations in physical education.
Online veröffentlicht: 22. Juli 2024
Gesehen am 30.10.2025